2018
DOI: 10.3892/ijmm.2018.3437
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide releasing molecule‑3 promotes the osteogenic differentiation of rat bone marrow mesenchymal stem cells by releasing carbon monoxide

Abstract: Stem cell‑based therapies are promising strategies to stimulate bone regeneration. Carbon monoxide releasing molecule‑3 (CORM‑3) exhibits multiple regulatory effects in a number of cells by releasing carbon monoxide (CO). The present study aimed to investigate the influence of CORM‑3 on the osteogenic differentiation of rat bone marrow mesenchymal stem cells (BMSCs). BMSCs were divided into five groups: A CORM‑3‑osteogenic group, in which cells were pretreated with CORM‑3 and subjected to osteogenic differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…RUNX2 belongs to the RUNX family and plays an important role in osteoblast differentiation and skeletal formation [23]. Moreover, RUNX serves as a biomarker for early stage of osteogenic differentiation while OCN and OPN are both osteoblast markers [24]. Therefore, induction of osteogenic differentiation would be accompanied by upregulation of RUNX1, OCN, and OPN.…”
Section: Discussionmentioning
confidence: 99%
“…RUNX2 belongs to the RUNX family and plays an important role in osteoblast differentiation and skeletal formation [23]. Moreover, RUNX serves as a biomarker for early stage of osteogenic differentiation while OCN and OPN are both osteoblast markers [24]. Therefore, induction of osteogenic differentiation would be accompanied by upregulation of RUNX1, OCN, and OPN.…”
Section: Discussionmentioning
confidence: 99%
“…The disparity between OP+EX and OP+COEX rats is not easily attributed to hormonal responses because leptin, adiponectin, and IGF‐1 levels were similar. CO does suppress osteoclastogenesis and stimulates osteoblastogenesis , yet because obesity alone did not result in bone loss, this is questionable. Instead and more plausibly, the further reduction in body mass caused by CO plus aerobic exercise was responsible for the differences in femoral material properties between OP+EX and OP+COEX rats.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel in vitro experiments using mouse bone marrow cells, the authors reported that CORM‐2 inhibited osteoclastogenesis by reducing receptor activator of nuclear factor‐κB ligand (RANKL) and oxidant production . In addition, CO was reported to increase proliferation of bone marrow mesenchymal stem cells and their differentiation into osteoblasts versus adipocytes . Indeed, diet‐induced obesity was shown to not only induce osteoclastogenesis, in part through RANKL activation, but also to increase bone marrow adipocyte expansion in mice and rats .…”
Section: Introductionmentioning
confidence: 99%
“…There is an abundance of preclinical evidence in both large and small animal models of diseases demonstrating the protective effects of CO at low concentrations (15-250 ppm) and CORMs, including hyperacute endotoxic shock [26], pulmonary inflammation [27], postoperative ileus [28], organ transplantation-induced ischemia-reperfusion injury [29,[30][31][32][33], airway hyperresponsiveness [34], necrotizing enterocolitis [35], and pulmonary hypertension [36]. CORM-3 has also been reported to promote the osteogenic differentiation of bone marrow mesenchymal stem cells by releasing CO [37].…”
Section: Discussionmentioning
confidence: 99%